Pelatihan Penanggulangan Perundungan di Kalangan Siswa Di SD Negeri 1505 Pasir Julu Kecamatan Sosa Kabupaten Padang Lawas - Junda Harahap; Nur Hakimah Akhirani Nasution; Amhar Maulana Harahap (Yayasan Perguruan Kampus, 2024)
Acts of violence in the world of education are currently an issue that is widely discussed because it has become quite an alarming phenomenon. On this basis, universities as institutions that have the role of providing enlightenment to the public must provide knowledge to the public regarding the prevention of violence in the world of education. This service activity aims to provide training to prevent bullying to school residents, especially teachers at SDN 1505 Pasir Julu. The method used in this training consists of an introductory phase, a formulation and solution phase, an implementation phase and a monitoring and evaluation phase. Meanwhile, the subjects in this training were teachers, student representatives, school committee and parent representatives at SD 1505 Pasir Julu. Based on the results of the analysis carried out after the implementation of the activities, the results obtained include (1). Prior to the implementation of the training, students, teachers, school committees and parent representatives did not know much about the concept of bullying in the world of education. (2). After being given structured training, information was obtained to increase knowledge and produce creative plans to prevent bullying at SDN 1505 Pasir Julu. The conclusion of this service activity is that violence prevention training is an effective effort to provide knowledge to school residents to increase awareness of bullying prevention in schools.